M-commerce success model / Zailani Abdullah and Md Yazid Mohd Saman - Abdullah, Zailani; Mohd Saman, Md Yazid (2004)
Mobile Commerce or M-Commerce is a next generation of E-Commerce. It's a new trend and is expected to drive the future development of E-Commerce. M-Commerce is a unique business opportunity and having its own unique characteristics and functions. Thus, M-Commerce can be generally defined as a process of conducting commercial transactions via "mobile" telecommunication networks using mobile devices, There are several technologies that are associated with the emerging of M-Commerce such as network and service communication technologies. Both technologies have gone through many evolution phases in order to fit with M-Commerce requirements. In this paper, we discuss issues in M-Commerce technologies, associated models and propose a model for M-Commerce called M-Commerce Success Model.